The great brain robbery - Bell, P. G. (Peter Gwilym) (Bell, P. G. (Peter Gwilym). Train to impossible places., 2019)
Suzy Smith and her troll friends gather for the relaunch of the Impossible Postal Express when a violent earthquake interrupt the ceremony and cause pandemonium in Tollville. Soon Suzy and her friends find themselves deep under Trollville tying to find who is threatening their land.